EFEKTIFITAS PELATIHAN KECERDASAN EMOSIONAL TERHADAP PENINGKATAN KECERDASAN EMOSIONAL PERAWAT DI RSU ROYAL PRIMA MEDAN: Training; Nurse; Emotional intelligence. - Sri Lestari Nasution (Jurnal Maternitas Kebidanan, 2020)
Emotional intelligence also determines a person's success. Emotional intelligence is an ability such as self-motivating ability, enduring to frustration, regulating mood so that stress loads don't paralyze thinking, and empathize. The purpose of this research is to analyze the effectiveness of emotional intelligence training on the enhancement of nurse emotional intelligence at Royal Prima Medan Hospital. This research is a quasi-experimental research with pretest-posttest design. The population in the study was the nurse of Royal Prima Medan Hospital and sampled as many as 38 respondents with provisions 19 for the experimental group and 19 for the control group. The data analysis methods used in this study are descriptive statistics and inferential statistics. The results showed: 1) Absence of increased or absence of emotional intelligence differences without emotional intelligence training (P = 0,310), 2) The emotional intelligence of nurses at Royal Prima Medan Hospital after given emotional intelligence training showed There is an increase or difference (P = 0,000).